Behavior Analysis of Building Structures After a Fire with FEA LISA V.8 - Aco Wahyudi Efendi (Department of Architecture, Faculty of Engineering, 2022)
Inspection of DPRD D office building by building inspection procedures using non-destructive inspection (NDT) method. By using the finite element method, the element discretization approach is used to solve the problem of finding the displacement of vertices/relations/lattices and structural forces. Discrete element equations are related to the matrix method for structural analysis and the results obtained are identical to those of classical analysis for structures. The discretization can be done with one-dimensional, two-dimensional or three-dimensional elements. LISA, a popular finite element analysis application, was used to estimate temperature rise for three different heat exchanger models. From the results of the behavior occurring in normal and post-combustion columns, it can be seen that there is a significant change in stress due to axial loading of the column and that the displacement behavior also changes quite significantly.Pemeriksaan bangunan gedung kantor DPRD D dengan metode pemeriksaan gedung menggunakan metode non-destructive inspection (NDT). Dengan analisis menggunakan Metode Elemen Hingga pendekatan diskritisasi elemen untuk menyelesaikan masalah pencarian perpindahan simpul/hubungan/kisi dan gaya struktural. Persamaan elemen diskrit terkait dengan metode matriks untuk analisis struktur dan hasil yang diperoleh identik dengan analisis klasik untuk struktur. Diskritisasi dapat dilakukan dengan elemen satu dimensi, dua dimensi atau tiga dimensi. LISA, aplikasi analisis elemen hingga yang populer, digunakan untuk memperkirakan kenaikan suhu untuk tiga model penukar panas yang berbeda. Dari hasil perilaku yang terjadi pada kolom normal dan pasca pembakaran terlihat adanya perubahan tegangan yang signifikan akibat pembebanan aksial kolom dan juga perilaku perpindahan yang berubah cukup signifikan.